PENGARUH KARAKTERISTIK PEKERJAAN DAN MODAL PSIKOLOGI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI MEDIASI (Studi pada PNS Sekretariat Daerah Kabupaten Blora) - Gemma Wahyu Intan Pratiwi, 1352020093 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the effect of job characteristics, psychological capital on job satisfaction of employees to achieve the performance of civil servants. The population in this study were all civil servants in the District Secretariat Blora. The sample in this study was 115 civil servants in the Secretariat Blora taken purposively. Data collection is done by using a questionnaire. Models built theoretical framework describes the variables mediating / intervening then to test 5 (five) hypotheses that have been developed to use multiple regression analysis with the model intervening (mediating) analysis technique using SPSS ver. 21. The test results show that the hypothesis of a significant effect of job characteristics and positive impact on job satisfaction, in addition to the characteristics of the work also shows the results of a significant and positive impact on the performance of civil servants, the psychological capital showed a significant and positive impact on job satisfaction, but on the other hand psychological capital has the result that no significant effect on the performance of civil servants and further job satisfaction significantly and positively impact on the performance of civil servants. Keywords: Job characteristics, Psychological Capital, Job Satisfaction and Employee Performance.